Case Report: Two cases of survival after complete transection of the left common carotid artery - Yang, Xin; Liu, Zhonglu; Sun, Qi; Mou, Yakui; Jia, Chuanliang; Zhang, Wenbin; Song, Fei; Li, Wen; Zhang, Hua; Song, Xicheng (Frontiers in Surgery, 2023)
Penetrating carotid artery traumas are rare yet fatal injuries with a high rate of mortality, and survivors may live with neurological sequelae. Of all the types of penetrating carotid artery traumas, the total transection of the common carotid artery (CCA) may be the most serious, can lead to death quickly, and have few reports of survivors. We described two cases of patients with the complete CCA transections who survived without any neurological sequelae. The penetrating neck traumas of both patients were confirmed as complete CCA severance by CT and surgical exploration. Case 1 received an insertion of an interposition PTFE graft to reconstruct the CCA, with postoperative ultrasound and CTA verifying the total occlusion. Case 2 underwent non-operative management under close observation and did not develop delayed active bleeding or neurological symptoms. Both patients recovered well, and no nervous system sequelae appeared during the follow-up period. Carotid artery injury cannot be ruled out in asymptomatic penetrating neck injury. If CTA is feasible given the patient’s hemodynamic condition, then it should be used as a routine examination to evaluate cervical vascular injury in patients with penetrating neck trauma. Management for hemodynamically stable carotid artery injury remains controversial. These two cases of transverse carotid artery injury have caused us to further consider the principles of this kind of case management.